Perceived weight discrimination among middle-aged and older adults in India: Results of a national survey in 2017-2018 - Supa Pengpid (2022)
This chapter aimed to estimate the prevalence and correlates of perceived weight discrimination in middle-aged and older adults in a national population survey in India. The sample included 72,262 middle-aged and older adults from a cross-sectional national community dwelling survey in India in 2017-2018. Results indicate that the prevalence of perceived weight discrimination was 0.3%, 0.3% among women, and 0.2% among men. Among participants with weight discrimination, the major discriminatory situations were less courtesy (82.2%), followed by service setting (65.3%), and less clever (64.4%). In the adjusted logistic regression analysis, no education and food insecurity were positively associated with perceived weight discrimination, while urban residence, Muslim and Christians were negatively associated with perceived weight discrimination. In addition, in unadjusted analysis, underweight was marginally significantly associated with perceived weight discrimination, while obesity was not significantly associated with perceived weight discrimination. A low proportion (0.3%) of middle-aged and older adults in India experienced weight discrimination, and several associated factors were identified that may be targeted to reduce weight discrimination.